(untitled) (Cadernos de Sociomuseologia, 2014)
From the understanding of Non-Formal Education linked to Museology, the article proposes a discussion that highlights the importance of reflecting on a specific public museums, their employees. Called internal public museums, the group that makes up part of the front office staff, occupies a strategic position in relation to maintaining the image of the institution and the satisfaction of museum visitors’ experience. Highlighted the strategic position of the group, this paper aims to arouse the interest of museum professionals for the thematic and stimulate action towards favoring the development of the ’forgotten’ public ’, both professionally and personally. The stimulus comes through the proposed establishment of a methodology for an educational program directed to museum employees as justifying its relevance to the museum. Key words: Museology and Education; Non-Formal Education; Educational Action; internal public